1991
DOI: 10.1017/s0021859600078229
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inflorescence removal on interactions between reproductive storage sites of field beans (Vicia faba) under different shading treatments

Abstract: SUMMARYIn studies of two indeterminate cultivars in field experiments in 1985 and 1986 at Hohenheim University, the hierarchy within the reproductive storage system of field bean plants was manipulated by removal of inflorescences at various growth stages and nodes. Shading reduced pod set and seed weight mainly at basal nodes. Increasing plant population density reduced seed yield traits at all nodes. Removal of basal inflorescences increased pod set and seed weight at the remaining nodes, especially the lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Continuous flower and pod removal from compea plants have been reported to prevent plants senescence and delay maturity. Aufhammer and Gotz-Lee (1991) revealed in field beans that removal of basel inflorescence increased pod set and seed weight at remaining nodes especially at the lower ones. Gwathmey et al (1992) showed that in compea, pod removal changed the reproductive pattern of senescent genotype.…”
Section: Introductionmentioning
confidence: 96%
“…Continuous flower and pod removal from compea plants have been reported to prevent plants senescence and delay maturity. Aufhammer and Gotz-Lee (1991) revealed in field beans that removal of basel inflorescence increased pod set and seed weight at remaining nodes especially at the lower ones. Gwathmey et al (1992) showed that in compea, pod removal changed the reproductive pattern of senescent genotype.…”
Section: Introductionmentioning
confidence: 96%
“…Such, plants in the field had to distribute the available resources among a higher number of flowers. Aufhammer and Götz-Lee (1991) reported that removing the three lowest inflorescences in faba bean increased the seed yield at the remaining inflorescences. A similar effect of redistributing reproductive efforts might take place in pollen production, resulting in a lower amount of pollen per single flower in the presence of many flowers.…”
Section: Effects Of Environment On Pollen Productionmentioning
confidence: 99%
“…Under normal growing conditions, genotypes and plants would highly vary for the number of flowers and, if their fertilization was no restriction, for their maximum possible seed set (Rowlands 1960). One inflorescence bears three to eight flowers, but rarely produces more than four pods, and only about 25 % of fertilized flowers develop into pods (Stoddard 1986; Aufhammer and Götz-Lee 1991). This excess of flowers is an ecological strategy to attract pollinators and a common feature in mixed-mating species (Patrick and Stoddard 2010), however, it impedes an interpretation of the resulting number of pods per plant in terms of autofertility since even the most autofertile plant would not achieve 100 % pods per flower.…”
Section: Introductionmentioning
confidence: 99%